Both basal and post-prandial muscle protein synthesis rates, following the ingestion of a leucine-enriched whey protein supplement, are not impaired in sarcopenic older males. Issue 5 (October 2017) - Kramer, Irene Fleur; Verdijk, Lex B.; Hamer, Henrike M.; Verlaan, Sjors; Luiking, Yvette C.; Kouw, Imre W.K.; Senden, Joan M.; van Kranenburg, Janneau; Gijsen, Annemarie P.; Bierau, Jörgen; Poeze, Martijn; van Loon, Luc J.C.
Summary: Background: Studying the muscle protein synthetic response to food intake in elderly is important, as it aids the development of interventions to combat sarcopenia. Although sarcopenic elderly are the target group for many of these nutritional interventions, no studies have assessed basal or post-prandial muscle protein synthesis rates in this population. Objective: To assess the basal and post-prandial muscle protein synthesis rates between healthy and sarcopenic older men. Design: A total of 15 healthy (69 ± 1 y) and 15 sarcopenic (81 ± 1 y) older men ingested a leucine-enriched whey protein nutritional supplement containing 21 g of protein, 9 g of carbohydrate, and 3 g of fat. Stable isotope methodology combined with frequent collection of blood and muscle samples was applied to assess basal and post-prandial muscle protein fractional synthetic rates. Handgrip strength, muscle mass, and gait speed were assessed to identify sarcopenia, according to international criteria. Results: Basal mixed muscle protein fractional synthetic rates (FSR) averaged 0.040 ± 0.005 and 0.032 ± 0.003%/h (mean ± SEM) in the sarcopenic and healthy group, respectively (P = 0.14). Following protein ingestion, FSR increased significantly to 0.055 ± 0.004 and 0.053 ± 0.004%/h in the post-prandial period in the sarcopenic (P = 0.003) and healthy groups (P < 0.001), respectively, with no differences between groups (P = 0.45). Furthermore, no differences were observed between groups in muscle protein synthesis rates during the early (0.058 ± 0.007 vs 0.060 ± 0.008%/h, sarcopenic vs healthy, respectively) and late (0.052 ± 0.004 vs 0.048 ± 0.003%/h) stages of the post-prandial period (P = 0.93 and P = 0.34, respectively). Conclusions: Basal muscle protein synthesis rates are not lower in sarcopenic older men compared to healthy older men. The ingestion of 21 g of a leucine-enriched whey protein effectively increases muscle protein synthesis rates in both sarcopenic and healthy older men. Public trial registry number : NTR3047.